2019
DOI: 10.1108/jedt-09-2018-0143
|View full text |Cite
|
Sign up to set email alerts
|

Critical drivers (CDs) of value management adoption in the Nigerian construction industry

Abstract: Purpose This paper aims to assess the drivers of value management (VM) in the Nigerian construction industry with a view to identify the critical ones through Delphi study. Design/methodology/approach A team of 15 carefully selected experts in VM were engaged in two rounds of Delphi survey, and the responses of the survey were analyzed with descriptive statistics (mean, standard deviation and mode). Kendall’s coefficient of concordance test and Chi-square (χ2) test were also used to test the level of consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Of these three, the deviation technique is the most used, followed by Kendall's coefficient of concordance. However, studies combining these approaches have also emerged in recent times (Ojo and Ogunsemi, 2019). Over time, the interquartile deviation (IQD) along with the median has been suggested by several studies as the most reliable deviation approach towards attaining consensus (Aigbavboa, 2013; Tengan and Aigbavboa, 2018; Hasson et al , 2000; Raskin, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these three, the deviation technique is the most used, followed by Kendall's coefficient of concordance. However, studies combining these approaches have also emerged in recent times (Ojo and Ogunsemi, 2019). Over time, the interquartile deviation (IQD) along with the median has been suggested by several studies as the most reliable deviation approach towards attaining consensus (Aigbavboa, 2013; Tengan and Aigbavboa, 2018; Hasson et al , 2000; Raskin, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…It has earlier been suggested that the chi-square should be adopted when the number of variables to be evaluated is larger than seven (Siegel and Castellan, 1988) as in the case of this current study, and consensus is termed as achieved when computed chi-square value is larger than the critical chi-square value derived (Tymvios and Gambatese, 2016). In a bid to achieve genuine consensus, this study followed the path of Ojo and Ogunsemi (2019) by combining the IQD, Kendall's W and X 2 technique. The Statistical Package for Social Sciences was used as a tool to achieve these analyses.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Oke and Aigbavboa (2017) revealed that since the introduction of VM into Nigeria in the 1990s, the application of VM on construction projects in the Nigerian construction industry remain minimal (Oke and Ogunsemi, 2013). Considering the year of VM introduction into the Nigerian construction industry, Ojo and Ogunsemi (2019) opined that VM ought to have been fully embraced into the Nigerian construction process. This shows the drag in the level of improving the services and skills of quantity surveyors in Nigeria.…”
Section: Mitigating Strategies Of Threats To Quantity Surveying Profession In the Nigerian Construction Industrymentioning
confidence: 99%
“…The SDs of most of the barriers in this study are approximately 1.00, except for "Negative attitude of employee (B14)" and "Time consuming for improving environmental performance (B20)" with SD of 1.57 and 1.69 respectively. This implies that the variability of the dataset of this study based on the opinions of the respondents is minimal (Oke and Aghimien, 2018;Ojo and Ogunsemi, 2019). Thus, in descriptive terms, the 20 barriers could be termed significant barriers to the implementation of EMS in the NCI.…”
Section: Resultsmentioning
confidence: 98%